Pengaruh Konten Media Sosial Instagram terhadap Citra Partai Keadilan Sejahtera: Survei pada Follower @pk_sejahtera - Ali Izah Robbani; Nani Nurani Muksin (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
The Public Relations of the Prosperous Justice Party (PKS) utilizes Instagram social media as a strategic platform to influence the party's image. PKS is portrayed as an Islamic-based political party that uses the path of da'wah in its political endeavors and strives to strengthen its image through content on Instagram social media. The objectives of this research are to measure 1) the content of the @pk_sejahtera Instagram social media, 2) the image of PKS, and 3) the influence of Instagram social media content on the image of PKS. The theories used are content pillars theory, image theory, and SOR (Stimulus-Organism-Response) theory. This research methodology uses a quantitative approach with a survey method and the sampling technique used is random sampling. The population consists of 2,577 followers of @pk_sejahtera on Instagram who commented or interacted on 68 content items related to activities, education, and entertainment from April 20 - May 20, 2025. The sample size is 96 respondents. Data collection techniques involved distributing closed online questionnaires. The research results show that variable X (credible, shareable, useful or fun, interesting, relevant, different, and on-brand) obtained an average value of 3.66 and is categorized as high, indicating that the presented content is positively evaluated, capable of attracting attention, clearly conveys messages, and builds engagement with its followers. Variable Y (visibility, clarity, and uniqueness) has an average value of 3.72 and is categorized as high, indicating that the image of PKS has been positively formed, appearing visible, clear, and unique. The influence of Instagram social media content on the image of PKS is obtained through an R Square value of 0.639 and a t-count value (12.908) > t-table (1.985), indicating a significant influence between Instagram social media content and the image of PKS, with 63.9% of the PKS image being influenced by Instagram social media content and the remaining 36.1% influenced by other factors outside the research variables. This research proves that Instagram social media content has a significant influence on the image of PKS.